Sharing Online Experiments – An Excellent Opportunity for Networking of Higher Education Institutions - Krneta, Radojka (International Journal of Interactive Mobile Technologies (iJIM), 2017)
The opportunity for networking of higher education institutions (HEIs) by networking of their remote laboratories (RLs) is considered in this paper. Several important issues regarding successful HEIs networking by networking of their RLs are highlighted and resulted from a round table discussion during Experiment@ International Workshop 2016 “The Emerging Technologies on the Internet of Everything “ -ETIoE’16.